Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To simplify the expression [tex]\(\frac{\left(3 y^4 n^6\right)^2}{\left(y^2 n^{-3}\right)^4}\)[/tex], we should start by simplifying both the numerator and the denominator separately:
1. Simplify the numerator:
[tex]\[ \left(3 y^4 n^6\right)^2 \][/tex]
Raise each term inside the parentheses to the power of 2:
[tex]\[ (3 y^4 n^6)^2 = 3^2 \cdot (y^4)^2 \cdot (n^6)^2 \][/tex]
Calculate each of these:
[tex]\[ 3^2 = 9, \quad (y^4)^2 = y^{4 \cdot 2} = y^8, \quad (n^6)^2 = n^{6 \cdot 2} = n^{12} \][/tex]
Therefore, the numerator is:
[tex]\[ 9 y^8 n^{12} \][/tex]
2. Simplify the denominator:
[tex]\[ \left(y^2 n^{-3}\right)^4 \][/tex]
Raise each term inside the parentheses to the power of 4:
[tex]\[ (y^2 n^{-3})^4 = (y^2)^4 \cdot (n^{-3})^4 \][/tex]
Calculate each of these:
[tex]\[ (y^2)^4 = y^{2 \cdot 4} = y^8, \quad (n^{-3})^4 = n^{-3 \cdot 4} = n^{-12} \][/tex]
Therefore, the denominator is:
[tex]\[ y^8 n^{-12} \][/tex]
3. Combine the simplified numerator and denominator:
[tex]\[ \frac{9 y^8 n^{12}}{y^8 n^{-12}} \][/tex]
Simplify the fraction by canceling out the common factors:
[tex]\[ \frac{9 y^8 n^{12}}{y^8 n^{-12}} = 9 \cdot \frac{y^8}{y^8} \cdot \frac{n^{12}}{n^{-12}} \][/tex]
Since [tex]\( \frac{y^8}{y^8} = 1 \)[/tex]:
[tex]\[ 9 \cdot 1 \cdot \frac{n^{12}}{n^{-12}} = 9 \cdot n^{12 - (-12)} = 9 \cdot n^{12 + 12} = 9 \cdot n^{24} \][/tex]
Therefore, the simplified expression is:
[tex]\[ 9 n^{24} \][/tex]
So, the correct answer is:
[tex]\[ \boxed{9 n^{24}} \][/tex]
1. Simplify the numerator:
[tex]\[ \left(3 y^4 n^6\right)^2 \][/tex]
Raise each term inside the parentheses to the power of 2:
[tex]\[ (3 y^4 n^6)^2 = 3^2 \cdot (y^4)^2 \cdot (n^6)^2 \][/tex]
Calculate each of these:
[tex]\[ 3^2 = 9, \quad (y^4)^2 = y^{4 \cdot 2} = y^8, \quad (n^6)^2 = n^{6 \cdot 2} = n^{12} \][/tex]
Therefore, the numerator is:
[tex]\[ 9 y^8 n^{12} \][/tex]
2. Simplify the denominator:
[tex]\[ \left(y^2 n^{-3}\right)^4 \][/tex]
Raise each term inside the parentheses to the power of 4:
[tex]\[ (y^2 n^{-3})^4 = (y^2)^4 \cdot (n^{-3})^4 \][/tex]
Calculate each of these:
[tex]\[ (y^2)^4 = y^{2 \cdot 4} = y^8, \quad (n^{-3})^4 = n^{-3 \cdot 4} = n^{-12} \][/tex]
Therefore, the denominator is:
[tex]\[ y^8 n^{-12} \][/tex]
3. Combine the simplified numerator and denominator:
[tex]\[ \frac{9 y^8 n^{12}}{y^8 n^{-12}} \][/tex]
Simplify the fraction by canceling out the common factors:
[tex]\[ \frac{9 y^8 n^{12}}{y^8 n^{-12}} = 9 \cdot \frac{y^8}{y^8} \cdot \frac{n^{12}}{n^{-12}} \][/tex]
Since [tex]\( \frac{y^8}{y^8} = 1 \)[/tex]:
[tex]\[ 9 \cdot 1 \cdot \frac{n^{12}}{n^{-12}} = 9 \cdot n^{12 - (-12)} = 9 \cdot n^{12 + 12} = 9 \cdot n^{24} \][/tex]
Therefore, the simplified expression is:
[tex]\[ 9 n^{24} \][/tex]
So, the correct answer is:
[tex]\[ \boxed{9 n^{24}} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.